The role of knowlegde transfer in increasing human resource productivity in Photokopi Coffee House Bondowoso - Alifian Nugraha; Andrias Dwimahendrawan; Bimantara Galuh Maulana (Institute of Computer Science (IOCS), 2023)
The aim to be achieved from carrying out this research is to analyze the role of knowledge transfer in increasing the productivity of human resources in Photokopi Coffee House Bondowoso. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation and document analysis. The research results show that knowledge transfer plays an important role in increasing the productivity of human resources at Photokopi Coffee House Bondowoso. Factors such as an organizational culture that supports learning, effective communication, and a good training system are key in the knowledge transfer process. Apart from that, collaboration between experienced employees and those who have just joined also has a positive impact in generating new knowledge and improving performance. This research contributes to business owners understanding the importance of knowledge transfer as a strategy to increase human resource productivity. The practical implications of this research are the importance of creating a work environment that supports knowledge exchange, developing effective training programs, and encouraging collaboration between employees. In this way, Photokopi Coffee House Bondowoso can continue to develop and compete sustainably in the creative coffee cafe industryThe aim to be achieved from carrying out this research is to analyze the role of knowledge transfer in increasing the productivity of human resources in Photokopi Coffee House Bondowoso. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation and document analysis. The research results show that knowledge transfer plays an important role in increasing the productivity of human resources at Photokopi Coffee House Bondowoso. Factors such as an organizational culture that supports learning, effective communication, and a good training system are key in the knowledge transfer process. Apart from that, collaboration between experienced employees and those who have just joined also has a positive impact in generating new knowledge and improving performance. This research contributes to business owners understanding the importance of knowledge transfer as a strategy to increase human resource productivity. The practical implications of this research are the importance of creating a work environment that supports knowledge exchange, developing effective training programs, and encouraging collaboration between employees. In this way, Photokopi Coffee House Bondowoso can continue to develop and compete sustainably in the creative coffee cafe industry.